Protozoan-Viral-Bacterial Co-Infections Alter Galectin Levels and Associated Immunity Mediators in the Female Genital Tract - Fichorova, Raina N.; DeLong, Allison K.; Cu-Uvin, Susan; King, Caroline C.; Jamieson, Denise J.; Klein, Robert S.; Sobel, Jack D.; Vlahov, David; Yamamoto, Hidemi S.; Mayer, Kenneth H. (Frontiers in Cellular and Infection Microbiology, 2021)
Co-infections with sexually transmittable pathogens are common and more likely in women with disturbed vaginal bacteriome. Among those pathogens, the protozoan parasite Trichomonas vaginalis (TV) is most common after accounting for the highly persistent DNA viruses human papillomavirus (HPV) and genital herpes. The parasitic infection often concurs with the dysbiotic syndrome diagnosed as bacterial vaginosis (BV) and both are associated with risks of superimposed viral infections. Yet, the mechanisms of microbial synergisms in evading host immunity remain elusive. We present clinical and experimental evidence for a new role of galectins, glycan-sensing family of proteins in mixed infections. We assessed participants of the HIV Epidemiology Research Study (HERS) at each of their incident TV visits (223 case visits) matched to controls who remained TV-negative throughout the study. Matching criteria included age, race, BV (by Nugent score), HIV status, hysterectomy, and contraceptive use. Non-matched variables included BV status at 6 months before the matched visit, and variables examined at baseline, within 6 months of and/or at the matched visit e.g. HSV-2, HPV, and relevant laboratory and socio-demographic parameters. Conditional logistic regression models using generalized estimating equations calculated odds ratios (OR) for incident TV occurrence with each log10 unit higher cervicovaginal concentration of galectins and cytokines. Incident TV was associated with higher levels of galectin-1, galectin-9, IL-1β and chemokines (ORs 1.53 to 2.91, p<0.001). Galectin-9, IL-1β and chemokines were up and galectin-3 down in TV cases with BV or intermediate Nugent versus normal Nugent scores (p<0.001). Galectin-9, IL-1β and chemokines were up in TV-HIV and down in TV-HPV co-infections. In-vitro, TV synergized with its endosymbiont Trichomonasvirus (TVV) and BV bacteria to upregulate galectin-1, galectin-9, and inflammatory cytokines. The BV-bacterium Prevotella bivia alone and together with TV downregulated galectin-3 and synergistically upregulated galectin-1, galectin-9 and IL-1β, mirroring the clinical findings of mixed TV-BV infections. P. bivia also downregulated TVV+TV-induced anti-viral response e.g. IP-10 and RANTES, providing a mechanism for conducing viral persistence in TV-BV co-infections. . Collectively, the experimental and clinical data suggest that galectin-mediated immunity may be dysregulated and exploited by viral-protozoan-bacterial synergisms exacerbating inflammatory complications from dysbiosis and sexually transmitted infections.